Purification of Andrographolide Methanolic Extract Using Molecularly Imprinted Polymer Prepared by Precipitation Polymerization - Wiwin Winingsih; Slamet Ibrahim; Sophi Damayanti (MDPI AG, 2022)
Molecularly Imprinted Polymer (MIP) has a specific cavity in which the conformity of shape, size, and functionalities corresponds with its template molecule and has been widely used in separation processes. Therefore, this study aims to examine the application of MIP for the purification of andrographolide. The MIP was synthesized by precipitation polymerization using methacrylic acid (MAA) and ethylene glycol dimethacrylate (EGDMA) as the functional monomer and cross-linker, andrographolide as a template, and acetonitrile:toluene (3:1) as porogen solvent. The results showed that the binding capacity of Synthesized MIP was 1.2486 mg/g, while the particle size was 295.5 nm with a polydispersity index of 0.064. Furthermore, the imprinting and selectivity factors were 1.148 and 12.37, respectively. The purification process by MIP increased the purity from 55.37 ± 0.69 to 94.94% ± 0.34, while the isolate characterization showed that purified andrographolide had a similar character compared to the standard.